Air Power in War. - Tedder, Arthur W. (University of Alabama Press, 1947)
Arthur Tedder, who was knighted and raised to the peerage for his contributions to the Allied victory in World War II, served in the British air force in World War I and played an important role in professionalizing and organizing British air forces between the two world wars. During World War II he held a succession of increasingly vital air force posts. In addition to his achievements as Air Commander-in-Chief in the North African theater early in the war, Tedder€s most lasting contribution was as Deputy Supreme Commander under Dwight D. Eisenhower. He deserves much credit for keeping t.